2004
DOI: 10.1021/jp048683i
|View full text |Cite
|
Sign up to set email alerts
|

I. Cesium Leaching in CsA and CsX Zeolites

Abstract: Sodium zeolite X and sodium zeolite A have been exchanged with cesium solutions prepared from three cesium salts (chloride, nitrate, and acetate). Depending on the solution, the cesium cations were found to be located in different sites of the zeolite networks. If cesium acetate solution is used, then cesium reaches sites SII and SIII in the large cavity whereas if nitrate or chloride solutions are put in contact with zeolites, cesium is positioned only in sites SIII. This distribution determines the leaching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 20 publications
3
20
1
Order By: Relevance
“…Safe retention depends on the location of cesium in the zeolite structure as shown in our previous paper [13]. We found that depending on the anions present in the exchange solution the cesium cations were located in different sites of the zeolite, A or X, network.…”
Section: Introductionsupporting
confidence: 69%
See 2 more Smart Citations
“…Safe retention depends on the location of cesium in the zeolite structure as shown in our previous paper [13]. We found that depending on the anions present in the exchange solution the cesium cations were located in different sites of the zeolite, A or X, network.…”
Section: Introductionsupporting
confidence: 69%
“…As described in our previous work [13], the framework of zeolite A heated at 1073 K is partially destroyed. A high amount of amorphous material is present.…”
Section: X-ray Diffractionmentioning
confidence: 53%
See 1 more Smart Citation
“…It is generally agreed that steaming promotes the removal of framework aluminum from zeolite structure to form amorphous aluminum oxides [10]. De-alumination induces modifications in the acidity as well as in the positions of the exchangeable cations into zeolite because of non-rigid character of such sites [11]. In order to characterize the variation in acidity or cation positions, probe molecules and spectroscopy are highly suitable.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies in cation exchanged synthetic zeolites have reported that these materials are susceptible to both radiation and thermally-induced amorphization [4,5,[12][13][14]. The same effect was observed in various types of natural cation exchanged zeolitic materials [15][16][17].…”
Section: Introductionmentioning
confidence: 61%